Genetics Selection Evolution - Boichard, Didier; Dekkers, Jack; Hayes, Helene; van der Werf, Julius; Montagu ledoux, Dominique
Genetics Selection Evolution is an open access, peer-reviewed, online journal dedicated to original research on all aspects of genetics and selection in domestic animal species and other species providing results of immediate interest for farm animals' genetics. With the vast, recent increase in the amount and spectrum of available genetic and genomic data, and the development of next-generation sequencing-based approaches, there is an ever-increasing requirement for the collaboration and successful integration of varied results, techniques, and methods in furthering the advancement of the future of animal genetics. Genetics Selection Evolution focuses on contributing to these developments by providing a high-visibility forum for the dissemination of relevant research and reviews that will prompt new insights and discussions as well as stimulate new research in the field. Genetics Selection Evolution invites basic, applied and methodological content that will aid the current understanding and the utilization of genetic variability in domestic animal species. Although the focus is on domestic animal species, research on other species is invited if it contributes to the understanding of the use of genetic variability in domestic animals. Genetics Selection Evolution publishes results from all levels of study, from the gene to the quantitative trait, from the individual to the population, the breed or the species. Contributions concerning both the biological approach, from molecular genetics to quantitative genetics, as well as the mathematical approach, from population genetics to statistics, are welcome. Specific areas of interest include but are not limited to: gene and QTL identification, mapping and characterization, analysis of new phenotypes, high-throughput SNP data analysis, functional genomics, cytogenetics, genetic diversity of populations and breeds, genetic evaluation, applied and experimental selection, genomic selection, selection efficiency, and statistical methodology for the genetic analysis of phenotypes with quantitative and mixed inheritance.